Micro-X-ray diffraction and chemical mapping of aged interfaces between cement pastes and Opalinus Clay. (April 2020) - Bernard, Ellina; Jenni, Andreas; Fisch, Martin; Grolimund, Daniel; Mäder, Urs
Abstract: The safety of a geological repository designed for deep storage of nuclear waste rests on the long-lived isolation properties of the geological environment and the engineered barrier system. To study the chemical and physical behaviour of cementitious/clayey interfaces, such interfaces have been collected during repeat sampling campaigns of the CI Experiment (Cement-Clay Interaction Experiment) at the Mont Terri rock laboratory (St. Ursanne, Switzerland, www.mont-terri.ch ) over the last decade. This study focuses on the advanced analysis by μ-XRD mapping to locate and identify the mineral phases on each side of the interface. The hydrates portlandite, ettringite and C–S–H present in the Portland cement (PC) were dissolved in contact with the Opalinus Clay (OPA) up to different depths (~0.2 mm for portlandite; ~1 mm for ettringite; completely depleted for C–S–H up to 0.1 mm and less visible on a 1-mm-depth) while the ettringite from ESDRED (a low-pH cement type) seems to be destabilized to a larger depth (≥3 mm). In contrast to former studies, calcite could not be clearly observed at the interface PC - OPA but was well developed at the interface ESDRED - OPA. The extent of reaction after 10 years is very small in both cases, and dissolution of clay minerals remains below detection. The identification of mineral phases involved in reactions facilitates the understanding of the processes, thus, will help to improve the reactive transport models used to simulate the evolution over long times. Highlights: Micro-X-ray diffraction (μ-XRD) is a powerful tool for spatially resolved (2D) phase identification in heterogeneous materials. μ-XRD measurements result in mineral distribution maps across claystone – concrete interfaces. In the concrete, ettringite, C–S–H and portlandite (if present) are not observed in layers parallel to the interface. Calcite precipitates evenly spread in the cement or concentrated at the interface depending on the type of cement.